Integrated, cross-sectoral psycho-oncology (isPO): a new form of care for newly diagnosed cancer patients in Germany - Michael Kusch; Hildegard Labouvie; Vera Schiewer; Natalie Talalaev; Jan C. Cwik; Sonja Bussmann; Lusine Vaganian; Alexander L. Gerlach; Antje Dresen; Natalia Cecon; Sandra Salm; Theresia Krieger; et al. (BMC, 2022)
Abstract Background The annual incidence of new cancer cases has been increasing worldwide for many years, and is likely to continue to rise. In Germany, the number of new cancer cases is expected to increase by 20% until 2030. Half of all cancer patients experience significant emotional and psychosocial distress along the continuum of their disease, treatment, and aftercare, and also as long-term survivors. Consequently, in many countries, psycho-oncological programs have been developed to address this added burden at both the individual and population level. These programs promote the active engagement of patients in their cancer therapy, aftercare and survivorship planning and aim to improve the patients' quality of life. In Germany, the "new form of care isPO" ("nFC-isPO"; integrated, cross-sectoral psycho-oncology/integrierte, sektorenübergreifende Psycho-Onkologie) is currently being developed, implemented and evaluated. This approach strives to accomplish the goals devised in the National Cancer Plan by providing psycho-oncological care to all cancer patients according to their individual healthcare needs. The term "new form of care" is defined by the Innovation Fund (IF) of Germany's Federal Joint Committee as "a structured and legally binding cooperation between different professional groups and/or institutions in medical and non-medical care". The nFC-isPO is part of the isPO project funded by the IF. It is implemented in four local cancer centres and is currently undergoing a continuous quality improvement process. As part of the isPO project the nFC-isPO is being evaluated by an independent institution: the Institute for Medical Sociology, Health Services Research, and Rehabilitation Science (IMVR), University of Cologne, Germany. The four-year isPO project was selected by the IF to be eligible for funding because it meets the requirements of the federal government's National Cancer Plan (NCP), in particular, the "further development of the oncological care structures and quality assurance" in the psycho-oncological domain. An independent evaluation is required by the IF to verify if the new form of care leads to an improvement in cross-sectoral care and to explore its potential for permanent integration into the German health care system. Methods The nFC-isPO consists of six components: a concept of care (C1), care pathways (C2), a psycho-oncological care network (C3), a care process organization plan (C4), an IT-supported documentation and assistance system (C5) and a quality management system (C6). The two components concept of care (C1) and care pathways (C2) represent the isPO clinical care program, according to which the individual cancer patients are offered psycho-oncological services within a period of 12 months after program enrolment following the diagnosis of cancer. The remaining components (C3-C6) represent the formal-administrative aspects of the nFC-isPO that are intended to meet the legally binding requirements of patient care in the German health care system. With the aim of systematic development of the nFC-isPO while at the same time enabling the external evaluators to examine its quality, effectiveness and efficiency under conditions of routine care, the project partners took into consideration approaches from translational psycho-oncology, practice-based health care research and program theory. In order to develop a structured, population-based isPO care program, reference was made to a specific program theory, to the stepped-care approach, and also to evidence-based guideline recommendations. Results The basic version, nFC-isPO, was created over the first year after the start of the isPO project in October 2017, and has since been subject to a continuous quality improvement process. In 2019, the nFC-isPO was implemented at four local psycho-oncological care networks in the federal state North Rhine-Westphalia, in Germany. The legal basis of the implementation is a contract for "special care" with the German statutory health insurance funds according to state law (§ 140a SCB V; Social Code Book V for the statutory health insurance funds). Besides the accompanying external evaluation by the IMVR, the nFC-isPO is subjected to quarterly internal and cross-network quality assurance and improvement measures (internal evaluation) in order to ensure continuous quality improvement process. These quality management measures are developed and tested in the isPO project and are to be retained in order to ensure the sustainability of the quality of nFC-isPO for later dissemination into the German health care system. Discussion Demands on quality, effectiveness and cost-effectiveness of in the German health care system are increasing, whereas financial resources are declining, especially for psychosocial services. At the same time, knowledge about evidence-based screening, assessment and intervention in cancer patients and about the provision of psychosocial oncological services is growing continuously. Due to the legal framework of the statutory health insurance in Germany, it has taken years to put sound psycho-oncological findings from research into practice. Ensuring the adequate and sustainable financing of a needs-oriented, psycho-oncological care approach for all newly diagnosed cancer patients, as required by the NCP, may still require many additional years. The aim of the isPO project is to develop a new form of psycho-oncological care for the individual and the population suffering from cancer, and to provide those responsible for German health policy with a sound basis for decision-making on the timely dissemination of psycho-oncological services in the German health care system. Trial registration The study was pre-registered at the German Clinical Trials Register (https://www.drks.de/DRKS00015326) under the following trial registration number: DRKS00015326 ; Date of registration: October 30, 2018.